Prescription auditing based on World Health Organization (WHO) prescribing indicators in a teaching hospital in North India - Marya Ahsan; Iram Shaifali; Ayaz Khurram Mallick; Hari Om Kumar Singh; Swetabh Verma; Amritanshu Shekhar (International Journal of Medical Research and Review, 2016)
Background: Prescription writing is an important means of therapeutic intervention by the doctor and reflects his approach towards safe prescribing. Complacency in prescribing results in errors which can even cause adverse effects. These errors can be detected through a prescription audit. We undertook this study to audit the out-patient department (OPD) prescriptions for completeness of prescription format, legibility and against the World Health Organization (WHO) prescribing indicators recommended to investigate rational use of drugs.Methods: OPD prescriptions were photographed from the pharmacy of a teaching hospital over a period of three months and 1274 prescriptions were audited. Prescriptions were evaluated for completeness of prescription format while legibility was graded as grade 1, 2 and 3. Prescriptions were also analyzed on the five WHO prescribing indicators.Results: An average of 4.02 ± 2.23 drugs were prescribed per prescription of which 39.01% were antibiotics. Though 79.2% drugs were prescribed from the Essential Drug List, none was prescribed by the generic name. Rate of injection use was 7.54% in our study. Registration number of the doctor was absent in 100% of the prescriptions. Errors such as omitting the mention of allergy status, follow-up advice and directions of use were common. Almost 8% prescriptions were illegible (grade3) and 66.8% were legible with difficulty (grade 2).Conclusion: Majority of the prescriptions were incomplete and poly-pharmacy was evident in our study. Regular auditing and feedback is necessary for imbibing safe prescribing practices. Doctors need to be made aware about the errors and the recommended guidelines.